Determinants of CEO compensation : stock option and corporate governance. - Chia, Sze Ying. (2008)
This paper analyzes two issues relating to the CEO compensation of US listed firm. Firstly, we investigate the determinants of the proportion of CEO compensation that is tied to stock options. Secondly, we investigate the impact of corporate governance mechanism on the level of CEO compensation.